2015
DOI: 10.5209/rev_rced.2015.v26.46360
|View full text |Cite
|
Sign up to set email alerts
|

Uso problemático de las redes sociales en estudiantes universitarios

Abstract: ResumenLos avances que están produciéndose en el ámbito académico con el surgimiento de herramientas de la Web 2.0 y el empleo masivo por parte de los estudiantes de las redes sociales para comunicarse entre ellos, está haciendo que el panorama educativo se encuentre ante unos desafíos a los que tiene que dar respuesta. La investigación que aquí se presenta tuvo como objetivo principal analizar el estado del empleo de la redes sociales por parte alumnado universitario, así como los posibles malos hábitos y uso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
2
9
0
10
Order By: Relevance
“…Regarding the social networks used by the students of the faculty of Accounting and Administration, and based on the results of the National Youth Survey (2010), AMIPCI (2013), as well as Turkey's (2013), Sánchez, Ruíz and Sánchez (2015) and Domínguez and López (2015), it is evident that the most popular social network among the students who participated in this study is Facebook, followed by YouTube, Instagram and +Google. In this respect, findings made by Quan-Haase and Young (2010) showed that 82% of university students reported they use Facebook several times a day.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the social networks used by the students of the faculty of Accounting and Administration, and based on the results of the National Youth Survey (2010), AMIPCI (2013), as well as Turkey's (2013), Sánchez, Ruíz and Sánchez (2015) and Domínguez and López (2015), it is evident that the most popular social network among the students who participated in this study is Facebook, followed by YouTube, Instagram and +Google. In this respect, findings made by Quan-Haase and Young (2010) showed that 82% of university students reported they use Facebook several times a day.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way technologies did, Social Network Sites (SNSs) have grown into a worldwide phenomenon in which people connect, communicate, and socialise (Campbell et al, 2016). SNSs are considered online spaces where people open a public or private profile in order to interact with worldwide communities (Chugh & Ruhi, 2018) linked by different interests and preferences (Abu-Shanab & Al-Tarawneh, 2015;Arnold & Paulus, 2010;Hatzipanagos & John, 2017;Rodríguez, Ruiz-Palmero, & Rivas, 2015;Vázquez-Martínez & Cabero-Almenara, 2015) and transcending the time and space spheres of traditional social networks. Especially used but not limited to young people, SNSs have contributed to change the rules of traditional ways of communication.…”
Section: Introductionmentioning
confidence: 99%
“…En especial, los universitarios utilizan los MMSS de forma habitual, la mayoría tiene perfiles en varias redes sociales (Gómez, Roses y Farias, 2012), que consultan sistemáticamente con múltiples finalidades (Gallardo, Marqués y Bullen, 2015). Existen investigaciones centradas en analizar el uso o abuso que hacen de los mismos, el tiempo que dedican a ello, y la finalidad preferente (Sánchez-Rodríguez, Ruiz-Palmero y Sánchez-Rivas, 2015), usos ligados a los procesos formativos (Del Moral y Villalustre, 2012) y al consumo de ocio digital (Viñals, Abad y Aguilar, 2014), etc. Sin embargo, el presente estudio se centra en determinar las dimensiones del ecosistema digital de los universitarios relacionadas con el uso que priman de los MMSS -que tienen a su alcance-, para favorecer los distintos procesos, tales como el aprendizaje, la interacción social, la creación de contenidos, el consumo online, el ocio y las actividades lúdicas online.…”
Section: Introductionunclassified